LITERATURE REVIEW: THE EFFECTIVENESS OF CLASSIC MUSIC THERAPY TOWARDS AUDITORY HALLUCINATION IN SCHIZOPHRENIA PATIENT [KAJIAN LITERATUR: EFEKTIVITAS TERAPI MUSIK KLASIK TERHADAP HALUSINASI PENDENGARAN PADA PASIEN SKIZOFERNIA] - Novita Susilawati Barus; Deborah Siregar (Universitas Pelita Harapan, 2020)
Auditory hallucinations are among the most common sensory perception disorder in schizophrenia patient. Patients with auditory hallucinations are often seen talking to themselves and even doing something dangerous. Music therapy is one of the non-pharmacological interventions that have the ability to improve, restore, and maintain physical, mental, emotional, social and spiritual health. This literature is intended to give a deeper article on the effectiveness of classical music therapy on auditory hallucinations in schizophrenic patients. The database that I used to obtain information is EBSCO, National Library, ProQuest and Google scholars, according to the inclusion criteria, namely the main source, articles published in 2012- 2016, English and Indonesian articles, experimental research articles and randomized controlled trials and full text in free pdf format. The result that I’ve got based on five articles that have been reviewed is classical music therapy can reduce the intensity of auditory hallucinations, provide comfort and helping patients feel calm. Giving classical music therapy to auditory hallucinations in schizophrenia is effective in reducing the intensity of auditory hallucinations, the patient feels comfortable and becomes calm. Suggestions for future researchers, conduct research on the type, frequency and duration of classical music therapy that is effective and can be used for patients with auditory hallucinations in schizophrenic patients.BAHASA INDONESIA Halusinasi pendengaran merupakan gangguan persepsi sensori yang paling sering dialami pasien dengan skizofrenia. Pasien dengan halusinasi pendengaran sering terlihat bercakap-cakap sendiri, dan bahkan melakukan sesuatu yang membahayakan. Terapi musik merupakan salah satu intervensi nonfarmakologis yang memiliki kekuatan untuk meningkatkan, memulihkan, dan memelihara kesehatan fisik, mental, emosional, sosial dan spiritual. Kajian literatur ini bertujuan untuk menggali artikel tentang efektivitas terapi musik klasik terhadap halusinasi pendengaran pada pasien skizofrenia. Database yang gunakan untuk mendapatkan sumber informasi adalah EBSCO, Perpusnas, ProQuest dan Google scholar, sesuai dengan kriteria inklusi yaitu primary source, artikel diterbitkan tahun 2012-2016, artikel bahasa Inggris dan bahasa Indonesia, artikel penelitian kuantitatif yang evidence based practice dengan menggunakan metode penelitian experiment dan randomized controlled trial dan full text berbentuk pdf dan tidak berbayar. Hasil yang ditemukan berdasarkan kelima artikel yang telah ditelaah bahwa terapi musik klasik dapat menurunkan intensitas halusinasi pendengaran, memberi rasa nyaman dan menjadikan pasien tenang. Pemberian terapi musik klasik terhadap halusinasi pendengaran pada skizofrenia efektif untuk menurunkan intensitas halusinasi pendengaran, pasien merasa nyaman dan menjadi tenang. Saran untuk peneliti selanjutnya, melakukan penelitian mengenai jenis, frekuensi dan durasi terapi musik klasik yang efektif serta dapat digunakan untuk pasien dengan halusinasi pendengaran pada pasien skizofrenia.